Immersive Historical Consciousness: A Case Study on Virtual Reality Integration and Meaningful Learning in Modern Islamic Boarding School - Zulfikar Yusuf; Nafik Muthohirin (Nadwa: Jurnal Pendidikan Islam, 2026)
Instructional activities in Sejarah Kebudayaan Islam (SKI), or Islamic Cultural History, are often teacher-centered, relying on lectures and memorization, which leads to limited student engagement. In response, Thursina International Islamic Boarding School has integrated Virtual Reality (VR) technology into SKI instruction to provide a more immersive learning experience. This study examines the implementation of VR in SKI learning and explores how it facilitates meaningful learning experiences for students. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis and analyzed using Miles and Huberman's interactive model of data condensation, data display, and conclusion drawing. The findings indicate that VR implementation involved selecting curriculum-aligned content, rotating its use among students, and utilizing it as a motivational reward for active participation. Meaningful learning was fostered through structured explanations, immersive visualization of historical events, and guided reflection following VR activities. Overall, the integration of VR enhanced student engagement and supported a deeper understanding of Islamic Cultural History. These findings suggest that immersive technologies can enrich Islamic education by promoting more engaging and meaningful learning experiences.